A social dilemma model of information self-disclosure, applied to the concussion domain. (October 2019) - Foster, Craig A; D'Lauro, Christopher; Johnson, Brian R
Under-reporting of concussions is a well-known public health problem. Unfortunately, concussion researchers and practitioners do not have an explicit theoretical foundation for understanding the psychology of concussion non-disclosure. We used interdependence theory, a theory based on the structure of social relationships, to develop a social dilemma model of personal information non-disclosure and apply it to the concussion domain. Self-disclosure becomes problematic when individuals perceive a need to report their concussions but also perceive that disclosure could be detrimental in some way. Individuals who experience these disclosure dilemmas can evaluate the value of concussion self-disclosure using direct outcomes (e.g. losing scholarships, improved recovery), self-concept outcomes (e.g. viewing disclosure as "weak" or "sensible"), and social status outcomes (e.g. being perceived poorly or favorably by teammates). These immediate, personal outcomes are integrated with relationship-specific motives and ethical considerations ultimately leading to disclosure or non-disclosure. Providing an explicit theoretical basis for self-disclosure dilemmas is critical for understanding concussion non-disclosure and mitigating its corresponding harm. Our social dilemma model highlights (a) the foundational psychological basis for concussion non-disclosure, (b) possible reasons that initiatives designed to increase concussion disclosure have been ineffective, and (c) the need to consider the decision-making autonomy of concussed individuals. Although we explain our social dilemma model using concussion self-reporting, we believe that this model is applicable to any domain where individuals are reluctant to disclose personal information to others who need it.